Surveillance Implementation Of Hiv/Aids In Jember Regency - irma Prasetyowati; adistha eka noveyani; Ni’mal Baroya; Wahyu Martina Sari; Heni Nuraini; Abdul Basith Qodam Ali; Ana Masfurotin Ni’mah; Dena Anggraeni Harjanto (Jurnal Ilmiah Kesehatan, 2021)
The number of people living with HIV/AIDS in Indonesia is increasing every year. HIV/AIDS surveillance is the most effective way to control the spreading of HIV/AIDS cases. This study aims to describe the implementation of HIV/AIDS surveillance in Jember. This paper was a descriptive study that included all public health centers (PHCs) conducting HIV/AIDS surveillance. The sample was the Jember District Departement of Health Office and four PHCs using purposive sampling. Variables in this study were input, process, and output. The data was obtained from an interview using a questionnaire. The results indicated that the four PHCs did not have an epidemiologist. Data collection mostly derived from Voluntary Counseling and Testing (VCT) and mobile VCT. Processing HIV/AIDS surveillance data utilized the HIV/AIDS and STDs Information System (SIHA) application and validated by the District Department of Health Office once a month. However, only two PHCs conducted analysis and data interpretation. Dissemination was only done by the District Departement of Health Office and 2 out of 4 PHCs. Hence, the components and process of surveillance needed to be optimized.